Primary hand rhabdomyosarcoma: A rare case report - Koç, Mustafa; Özercan, Reşat (My University, 2017)
Rhabdomyosarcomas are malignant, soft tissue tumors with striated muscle origin. Malignant round cell tumors are the common malignancy of childhood. The primary localizations are head and neck and genitourinary system. Only 7 % of lesion is seen in the upper extremity. Primer hand involvement is rare. In this article, we presented a 16-year-old girl who admitted to our clinic with acomplaint of a painful mass that grew rapidly in the left hand thenar area. Imaging findings revealed a heterogeneous solid mass lesion between the 1st and 2nd fingers, which showed dense contrast enhancement, approximately 6x5x7 cm in size, leading to destruction in the bony structures. A histopathological examination of the mass indicated alveolar rhabdomyosarcoma. We decided to present this rare entity with the radiological imaging findings.
Keywords: Patoloji; Onkoloji; Cerrahi